Stenting to prevent esophageal stricture after circumferential endoscopic submucosal dissection: an experimental study - Martinek, Jan; Dolezel, Radek; Walterova, Bara; Kollar, Marek; Juhas, Stefan; Juhasova, Jana; Vackova, Zuzana; Hustak, Rastislav; Erben, Jakub (Endoscopy international open, 2020)
Background and study aims Circular ESD (CESD) is a treatment option for patients with extensive early esophageal cancer. Its major drawback is the development of a stricture. Stenting may represent an attractive prevention strategy. We designed an experimental study to assess the effect of stents covered with acellular biomatrix (AB) and a drug-eluting stent. Materials and methods Thirty-five 35 pigs underwent CESD and were randomized into six groups: G1 (control), G2 (SEMS), G3 (SEMS + AB), G4 (SEMS + AB + steroid-eluting layer), G5 (biodegradable stent [BD]), G6 (BD + AB). SEMS were placed alongside the post-CESD defect, fixed and removed after 21 days. The main outcomes were stricture development, severity, and histopathology. Results Pigs with BD stents (G5, 6) experienced severe inflammation and hypergranulation without biodegradation, therefore, these groups were closed prematurely. Significant strictures developed in 29 of 30 pigs (96.7 %). The most severe stricture developed in G2 and G4 (narrowest diameter (mm) 8.5 ± 3, 3 (G2) and 8.6 ± 2.1 (G4) vs. 17 ± 7.3 (G1) and 13.5 ± 8.3 (G3); P < 0.01. Signs of re-epithelization were present in 67 % and 71 % in G1 and G2 and in 100 % in G3 and G4. The most robust re-epithelization layer was present in G4. The inflammation was the most severe in G1 (mean score 2.3) and least severe in G4 (0.4). Conclusions Stenting did not effectively prevent development of post-CESD esophageal stricture. SEMS with AB resulted in improved re-epithelization and decreased stricture severity. Steroid-eluting SEMS suppressed inflammation. BD stents seem inappropriate for this indication.